How transformative is agroecological knowledge co-creation? Insights from a systematic literature review - Bello Cartagena, Laura (2024)
Knowledge co-creation (KCC) is imperative for agroecological development, yet the extent to which agroecological KCC processes balance scientific rigor, local relevance, and legitimacy, and the extent to which they connect to transformative agroecological farming remains poorly understood. Therefore, we systematically reviewed 58 peer-reviewed empirical studies that involved agroecological KCC. While we did not find a connection between the perceived credibility, salience, and legitimacy of the co-created knowledge and impacts on agroecological farming, we did find that KCC processes had mostly incremental, rather than transformative, impacts. We conclude that an increased focus on agroecological principles, going beyond agroecological practices, is needed.